THE IMPLEMENTATION OF READING INSTRUCTION IN EFL CLASSROOM - Pustika, Reza; Wiedarti, Pangesti (ETERNAL (English, Teaching, Learning, and Research Journal), 2019)
ABSTRACT: The aim of this research is to investigate the implementation of reading instruction in EFL classroom. The method used was a survey research. The data for this research was gathered by distributing a questionnaire. The questionnaire was formulated based on the theories of experts about the ideal reading instruction. The data were analyzed descriptively by looking at the percentage of choice derived from the subjects of the research. This research discussed six best characteristics of reading instruction. It also presented six less implemented characteristics of reading instruction in EFL classroom.